Is non-operative management feasible for splenic injury due to colonoscopy?. (17th June 2013) - Guner, Ali; Kaya, Umit; Kece, Can; Kucuktulu, Uzer
Abstract : Colonoscopy is a widely used diagnostic and therapeutic procedure. While it is a relatively safe procedure, there is a risk of some complications. Splenic injury after colonoscopy is a very rare but a life-threatening complication; around 105 cases have been reported in the literature so far. Owing to the rarity of this complication, no management standards were defined. In the literature, most of the patients were managed with operative intervention and less frequently with observation. We report a case of splenic injury and massive hemoperitoneum due to colonoscopy treated non-operatively.